Creating High Value, Integrated Approaches to Mitigate Children's Complex Medical, Social and Relational Health Risks: Validation and National Findings on the Whole Child Complexity Index. (15th September 2021) - Bethell, Christina; Blackwell, Courtney; Garner, Andrew; Davis, Martha; Bruner, Charles
Abstract : Research Objective: To address the need for whole‐child assessments of risk to inform the many innovative national, state, and local efforts underway to promote whole‐child well‐being, we sought to: (1) develop and validate a risk index that acknowledges the complexity of the medical, social, and relational health risks children may simultaneously experience; (2) discern associations across types of risks and whether and to what extent relational and social health risks uniquely contribute to children's medical health risks, their healthcare utilization, and positive health outcomes; and (3) provide a baseline national and state level epidemiologic profile on a valid, whole‐child indicator of children's complex risks useful for the analyzing the need for and impact of policies and programs over time. Study Design: Data from the 2016–2019 National Survey of Children's Health were used to create and validate the Whole Child Complexity Index (WCCI) assessing children's complex medical, social and relational health risks. Confirmatory factor analysis (CFA) and convergent/divergent regression analyses were employed to assess validity. National and state sociodemographic variations were evaluated and each state's findings compared to assess variations that may inform policy. Population Studied: US children and youth age 0–17. Principal Findings: CFA validated the WCCI 3‐domain structure. Children with risks on more domains were more likely to have emergency and forgone care and less likely to flourish and engage/be ready to engage in school. Outcomes for children with only social health risks (SHR) and relational health risks (RHR) were similar to those experiencing only medical health risks (MHR), yet the former group was 5.75 times more likely to experience forgone care. Most children with MHR experienced SHR and/or RHR (64.3%). Wide variations across states was observed. Nearly one‐third (28.8%; publicly insured: 46%‐state range 35.2%–53.2%) experienced risks on two or more domains; 8.8% on all three domains (16.2% publicly insured). Wide household income and race/ethnicity disparities in were observed, yet, the WCCI accounted for variations in study outcomes. Conclusions: The WCCI sets a high bar to qualify for risk and is a valid, robust indicator of the complexity of medical, social and relational health risks children experience. RHR are prevalent, distinct from SHR, and significantly associated with worse outcomes for children with MHR and/or SHR. Substantial variations in prevalence of complex risks across states and sociodemographic populations of children present important opportunities to promote equity and improve child health by proactively assessing and address complex social, relational as well as medical health needs. Implications for Policy or Practice: The coronavirus pandemic has highlighted the reality that our children's physical, social and relational lives are inextricably intertwined and collectively promote or diminish both their early development and lifelong well‐being. Prior to the pandemic, child well‐being in the US has lagged behind other developed countries, and large socioeconomic inequities persist. The Whole Child Complexity Index provides a national and across state profile of opportunities to promote a whole child health policy and is useful to inform innovative, cross‐sector efforts that promote equitable whole‐child well‐being, prevent and mitigate risks, reduce avoidable medical health care costs and pay for high‐value care. Primary Funding Source: The Robert Wood Johnson Foundation.